Factors associated with in utero fetal death at the Bunyakiri General Reference Hospital, Kalehe Territory, in the east of the Democratic Republic of Congo - MWISHA LUKOO Freddy; Bagalwa Buhendwa Freddy; Bashona Cimanuka André; Mugisho Mirindi Théodore; Bweswa Wenda Merci; Ngongo Mutuka Evariste; Bogenda M’oa Lavie; Chatechirwe Masomo Potien (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2025)
Worldwide, 65 million third-quarter MFIUs take place each year, 98% of them located in countries with low Gross Industrial Product. The objective is to determine the factors associated with intrauterine fetal death in the Bunyakiri Rural Health Zone. Material and methods: this is a retrospective cross-sectional study carried out on 73 parturients whose fetuses died in utero in pregnancies of gestational age greater than 22 weeks of amenorrhea. This study was carried out from January 1, 2020 to December 31, 2023 at the maternity ward of the obstetrics department of the Bunyakiri General Reference Hospital. Results: For the entire study period, 8.7% cases of stillbirths were recorded. The majority of respondents were over 30 years old, i.e. 65.2%; 100% were from the rural area; 69.6% had a level of primary education and major multi-gestures. The cessation of active fetal movements was the reason for consultation for 71% of cases and 88.4% did not follow CPN. The age of pregnancy varies between 28 and 36 weeks of amenorrhea, or 72.5% of cases. A history of eclampsia and high blood pressure were recorded for 29%. On physical examination, the absence of fetal heart sounds (BCF) was noted for 97.1%, 58% had a uterine height between 28 and 30 cm and 100% of them had benefited from ultrasound. Blood count revealed leukocytosis in 87.1%. The associated pathologies are retroplacental hematoma (DPPNI) and eclampsia in 29% and 23.2% of cases. The treatment instituted was induction of labor with Misoprostol, i.e. 55.1%, and delivery hemorrhages were observed in 50.7% of cases and 85% delivered premature stillbirths. Conclusion: The implementation of refocused prenatal consultations and early detection of factors associated with in utero fetal death could significantly reduce the frequency of this stillbirth.